2017
DOI: 10.5888/pcd14.160549
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Pilot of a Randomized Faith-Based Intervention to Reduce Secondhand Smoke Exposure Among Korean Americans

Abstract: IntroductionInterventions are needed to prevent exposure to secondhand smoke (SHS), which persists in certain immigrant enclaves, including Koreans in the United States. A faith-based and culturally acceptable intervention was developed and pilot tested in collaboration with Korean churches to address SHS exposure among people of Korean descent.MethodsA pilot cluster randomized intervention trial was conducted with 11 Korean churches in southern California and 75 Korean adults who were exposed to SHS. Study pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 17 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…The samples were primarily adults aged 18 years and older (mean age ranged 35-70). Of 14 reviewed studies, 10 used a randomized controlled trial (RCT) with two groups (Hughes, Corcos, Hovell, & Hofstetter, 2017;Islam et al, 2013;K. B. Kim et al, 2014; M. T. Kim et al, 2011;S.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The samples were primarily adults aged 18 years and older (mean age ranged 35-70). Of 14 reviewed studies, 10 used a randomized controlled trial (RCT) with two groups (Hughes, Corcos, Hovell, & Hofstetter, 2017;Islam et al, 2013;K. B. Kim et al, 2014; M. T. Kim et al, 2011;S.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Of 14 reviewed studies, eight (Fang et al, 2006;Hughes et al, 2017; S. S. Kim, 2017; S. S. Kim, Kim, Fang, et al, 2015; M. T. Kim, Kim, Huh, et al, 2015;McDonnell et al, 2011;Moskowitz et al, 2016;Zhu et al, 2012) reported a specific Note. T2DM = type 2 diabetes mellitus; BP = blood pressure; BMI = body mass index; WC = waist circumference; W/H ratio = waist-to-hip ratio; f/u = follow-up; IG = intervention group; CG = control group; SHS = second hand smoking; CVD = cardiovascular disease; CHW = community health worker; RCT = randomized controlled trial (continues).…”
Section: Use and Usefulness Of Theorymentioning
confidence: 99%
See 3 more Smart Citations